Análise funcional de um consórcio microbiano de solo e prospecção de genes envolvidos na desconstrução da biomassa - Lima, Milena Tavares [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The deconstruction of lignocellulose by the action of microorganisms is an essential process for the carbon cycle and the conversion of biomass into fuels and chemicals. A wide variety of carbohydrates found in plant cell walls requires a multitude of enzymes for their degradation. The aim of this study was to isolate a microbial consortium of soil sample containing bagasse cane sugar decomposition, which is efficient in the deconstruction of biomass and the total DNA sequence for the isolation of genes involved in the deconstruction of lignocellulose. The biomass degrading microbial consortium was obtained from soil sample cultivated with sugarcane decomposed and shown to be efficient in the degradation of a potential lignocellulosic substrate, sugarcane bagasse. To prove the efficiency of the release of sugar from the biomass potential to be used in fermentation processes chromatographic analysis of sugars was performed when the number of microorganisms were cultivated only in a medium containing cane bagasse as a source of carbon. This test showed the release of glucose in the culture medium. Similarly, microbiological tests have shown that the production of hydrolytic enzymes such as cellulases and amylases have been made. The sequencing of total DNA extracted from the samples cultured in medium with cellulose consortium made possible the identification of microorganisms present in the consortium. Through these sequences to search for genes involved in the degradation of biomass and this assessment was also carried the genes of the enzymes alpha amylase, glucoamylase, alpha- glucosidase, beta glucosidase and endoglucanase enzymes of paramount importance in the process of deconstruction of lignocellulose found. All genes of the enzymes were similar to sequences of the bacterium Burkholderia sp SJ98, which has been described in the literature as an efficient organism in biodegradation of different compounds. Thus in the present ...

A desconstrução da lignocelulose pela ação dos microrganismos é um processo essencial para o ciclo do carbono e para a conversão da biomassa em combustíveis e produtos químicos. A extensa variedade de carboidratos encontrados na parede celular das plantas requer uma multiplicidade de enzimas para sua degradação. O objetivo desse trabalho foi isolar um consórcio microbiano de amostra de solo, contendo bagaço de cana-de-açúcar em decomposição, que fosse eficiente na desconstrução da biomassa e sequenciar o DNA total para isolamento de genes envolvidos na desconstrução da lignocelulose. O consórcio microbiano degradador de biomassa foi obtido através de amostra de solo cultivado com cana de açúcar em decomposição e mostrou ser eficiente na degradação de um potencial substrato lignocelulósico, o bagaço de cana. Para se comprovar a eficiência na liberação de açúcar da biomassa com potencial de ser usado em processos fermentativos foi realizada a análise cromatográfica de açúcares, quando esse conjunto de microrganismos foi cultivado em meio contendo apenas bagaço de cana como fonte de carbono. Esse ensaio mostrou a liberação de glicose no meio de cultivo. Do mesmo modo, foram realizados testes microbiológicos que mostraram a produção de enzimas hidrolíticas como celulases e amilases. O sequenciamento do DNA total extraído das amostras do consórcio cultivadas em meio com celulose possibilitou a identificação dos microrganismos presentes no consórcio. Através dessas sequencias também foi realizada a prospecção de genes envolvidos na degradação da biomassa e nessa avaliação foram encontrados os genes das enzimas alfa amilase, glucoamilase, alfa glucosidase, beta glucosidase e endoglucanase, enzimas de suma importância no processo de desconstrução da lignocelulose. Todos os genes das enzimas foram similares a sequencias da bactéria Burkholderia sp SJ98, que já foi descrita na ...
Keywords: Cana-de-açúcar; Bagaço de cana; Enzimas; Genes; Lignocelulose; Biomassa; Enzymes